Inflammatory profile discriminates clinical subtypes in LRRK2‐associated Parkinson's disease. (February 2017) - Brockmann, K.; Schulte, C.; Schneiderhan‐Marra, N.; Apel, A.; Pont‐Sunyer, C.; Vilas, D.; Ruiz‐Martinez, J.; Langkamp, M.; Corvol, J.‐C.; Cormier, F.; Knorpp, T.; Joos, T. O.; et al.
Abstract : Background and purpose: The presentation of Parkinson's disease patients with mutations in the LRRK2 gene (PDLRRK 2 ) is highly variable, suggesting a strong influence of modifying factors. In this context, inflammation is a potential candidate inducing clinical subtypes. Methods: An extensive battery of peripheral inflammatory markers was measured in human serum in a multicentre cohort of 142 PDLRRK 2 patients from the MJFF LRRK2 Consortium, stratified by three different subtypes as recently proposed for idiopathic Parkinson's disease: diffuse/malignant, intermediate and mainly pure motor. Results: Patients classified as diffuse/malignant presented with the highest levels of the pro‐inflammatory proteins interleukin 8 (IL‐8), monocyte chemotactic protein 1 (MCP‐1) and macrophage inflammatory protein 1‐β (MIP‐1‐β) paralleled by high levels of the neurotrophic protein brain‐derived neurotrophic factor (BDNF). It was also possible to distinguish the clinical subtypes based on their inflammatory profile by using discriminant and area under the receiver operating characteristic curve analysis. Conclusions: Inflammation seems to be associated with the presence of a specific clinical subtype in PDLRRK 2 that is characterized by a broad and more severely affected spectrum of motor and non‐motor symptoms. The pro‐inflammatory metabolites IL‐8, MCP‐1 and MIP‐1‐β as well as BDNF are interesting candidates to be included in biomarker panels that aim to differentiate subtypes in PDLRRK 2 and predict progression.